2008
DOI: 10.1152/physiolgenomics.00189.2007
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the QTL for sleep homeostasis in mice:Homer1ais a likely candidate

Abstract: Electroencephalographic oscillations in the frequency range of 0.5–4 Hz, characteristic of slow-wave sleep (SWS), are often referred to as the delta oscillation or delta power. Delta power reflects sleep intensity and correlates with the homeostatic response to sleep loss. A published survey of inbred strains of mice demonstrated that the time course of accumulation of delta power varied among inbred strains, and the segregation of the rebound of delta power in BxD recombinant inbred strains identified a genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 56 publications
4
44
0
Order By: Relevance
“…More crucially, however, studies in mice show that the increase in NREM SWA after sleep deprivation is also under genetic control (Franken et al 2001). It was found that Dps1, a quantitative trait locus (QTL) on mouse chromosome 13, accounts for 49% of the genetic variance in this trait (Franken et al 2001;Andretic et al 2008a), and the immediate early gene Homer1a was singled out as a likely candidate gene to carry the homeostatic signal within Dps1 (Maret et al 2007;Mackiewicz et al 2008;Curie et al 2013). Homeostasis is believed to be mainly reflected not in the levels of SWA per se but in the speed of wake-dependent accumulation and sleep-dependent dissipation of SWA.…”
Section: Slow Wave Activity and Sleep Homeostasis In Mammalsmentioning
confidence: 99%
“…More crucially, however, studies in mice show that the increase in NREM SWA after sleep deprivation is also under genetic control (Franken et al 2001). It was found that Dps1, a quantitative trait locus (QTL) on mouse chromosome 13, accounts for 49% of the genetic variance in this trait (Franken et al 2001;Andretic et al 2008a), and the immediate early gene Homer1a was singled out as a likely candidate gene to carry the homeostatic signal within Dps1 (Maret et al 2007;Mackiewicz et al 2008;Curie et al 2013). Homeostasis is believed to be mainly reflected not in the levels of SWA per se but in the speed of wake-dependent accumulation and sleep-dependent dissipation of SWA.…”
Section: Slow Wave Activity and Sleep Homeostasis In Mammalsmentioning
confidence: 99%
“…The c-Fos-null animals have more wakefulness and reduced slow wave sleep, and the Gria3 animals show dampened EEG powers across waking and NREM sleep but no changes in total sleep amount (Shiromani et al 2000;Steenland et al 2008). The Homer1a gene was also identified in QTL analysis as a strong candidate for a gene underlying sleep homeostasis and magnitude of delta power (Maret et al 2007;Mackiewicz et al 2008). More recent work by Gilestro et al (2009) monitored the expression of synaptic genes over the course of the normal sleep:wake cycle, as well as following periods of sleep deprivation in Drosophila.…”
Section: Genes Important For Synaptic Modulationmentioning
confidence: 99%
“…Homer1a gene expression is strongly linked with learning and neuronal activity (15). Accordingly, Homer1a mRNA is low during sleep and increases during wake, especially after sleep deprivation (19, 20). However, Homer1a protein is targeted to the PSD in the sleep phase (Fig.…”
mentioning
confidence: 99%